Conservative Management of Gestational Hypercalcemia Due to Primary Hyperparathyroidism with Lack of Complications - Di Bari, Flavia; Vita, Roberto; Marini, Herbert; Borrielli, Irene; Lo Re, Carmela; Panebianco, Vincenzo; Benvenga, Salvatore (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Introduction: Primary hyperparathyroidism (PHPT) is rare in pregnancy. PHPT and hypercalcemia are associated with negative maternofetal outcomes. Therefore, an early diagnosis and adequate treatment are essential. Case Presentation: We described the case of a pregnant woman complaining of nausea, vomiting and weight loss. Diagnosis of gestational PHPT (GPHPT) was made based on elevated serum calcium and parathyroid hormone levels (3.4 mmol/L and 41.6 pmol/L). Neck ultrasound documented a nodule suggestive of enlarged parathyroid, whereas the abdomen ultrasound revealed renal microlithiasis. Conservative treatment was started with oral hydration and a low-calcium diet. Clinical and biochemical monitoring was weekly and multidisciplinary. Despite our suggestion, the patient refused parathyroidectomy in the second trimester. Additional intravenous fluid rehydration from the 15th to the 25th week of gestation ameliorated the symptoms rapidly, and reduced calcium levels progressively from the 23rd week. At week 40, the woman gave birth to a healthy girl. At month 8 postpartum, calcemia and PTH were still elevated, and accompanied by osteoporosis and nephrocalcinosis. Surgery was accepted, and a parathyroid adenoma was removed. Conclusion: In the absence of guidelines for GPHPT management, its treatment should be individualized. In our case, despite high calcium levels, conservative treatment with strict monitoring led to a positive outcome of pregnancy.
Keywords: pregnancy